Promotion of Technical Entrepreneurship:Role of Humanities and Social Sciences - Babu Rao, G. (Journal of Engineering Education Transformations, 1999)
Technical Manpower is the greatest and valuable asset to India. We are the second largest scientific and technical force in the comity of nations with proven capabilities and performance in the progress of the world.